Effect of Neutron Fluence Rate on Irradiation Embrittlement of Low-copper RPV Steel - WU Yazhen, LI Guoyun, WANG Haidong, HUANG Juan, ZHANG Haisheng, SUN Kai, LEI Yang, ZHU Lini (Yuanzineng kexue jishu)
The reactor pressure vessels (RPVs) of pressurized water reactor (PWR) nuclear power plants currently in operation and under construction in China are all made of low-alloy ferritic steels obtained by quenching and tempering treatments (which meet the specification requirements of 16MND5 or A508-3) with Cu≤0.08wt%. In this paper, the influence of neutron fluence rate difference between reactor surveillance capsules and accelerated irradiation tests in research reactor was studied by the results of the 49 commercial reactor surveillance capsules and the 18 irradiation tests on High Flux Engineering Test Reactor (HFETR) and the Minjiang Test Reactor (MJTR). The results indicate that ductile brittle transition temperature (DBTT) increment of low-copper RPV steels is influenced by both neutron fluence and neutron fluence rate, the DBTT increase caused by higher neutron fluence rates is more significant when the neutron fluences are comparable, and the DBTT increment of higher neutron fluence is observed to be larger when the neutron fluence rates are comparable. It is found that lower neutron fluence rate (≤1×1012 cm−2·s−1, E＞1 MeV) has no effect on the ductile-to-brittle transition temperature of low-copper RPV steels. When evaluating low-copper RPV steels, if the neutron fluence rate is no more than 1×1012 cm−2·s−1, it is not necessary to correct the embrittenment caused by the neutron fluence rate difference between reactor surveillance capsules and research reactor data. Meanwhile, there is no uniform international conclusion on the fluence rate effect when neutron fluence rate ＞1×1012 cm−2·s−1, and high neutron fluence rate (＞1×1012 cm−2·s−1) in test reactors is more significant than that caused by low neutron fluence rate (≤1×1012 cm−2·s−1) in surveillance capsule. As well, the irradiation embrittlement calculation models such as RG1.99 (Rev. 2) in the United States, JEAC4201 in Japan, and FIS in France are not fully applicable to the changing trends of low-copper RPV steels in China. Without considering the influence of chemical composition, a simple exponential fitting was performed to obtain the relationship between ductile brittle transition temperature increment and neutron fluence. Furthermore, the normalized results for different neutron fluence and neutron fluence rate were obtained, and found the correlation with the different neutron fluence rate results of commercial PWRs and research test. It is of great significance to convert the rapid irradiation test of the research test reactor into the transition temperature rise of the pressure vessel under actual service conditions, which can more accurately and reliably verify the design life and assess the remaining service life of the pressure vessel, and at the same time provide reliable data for the design of the pressure vessel of the newly-built nuclear power plant.